Incidence and Progression of Lower Urinary Tract Symptoms in a Large Prospective Cohort of US Men - Platz, Elizabeth A. (2012)
PURPOSE: To support trials testing lifestyle interventions for lower urinary tract symptoms (LUTS), often a consequence of benign prostatic hyperplasia (BPH), we estimated LUTS incidence and progression rates in US men unselected for BPH. METHODS: We studied men in the Health Professionals Follow-up Study who we asked to report periodically by mailed survey whether they had had surgery or used medications for LUTS and to complete the International Prostate Symptom Score (IPSS) survey. For incidence, we included 25,879 men with an IPSS of 0–7 and no surgery history, who were followed 1992–2008. Incident “moderate or worse” LUTS (N=6,058) was defined as IPSS of ≥15, surgery, or medication use. “Modest or worse” LUTS was similarly defined but with IPSS≥8 (N=11,352). For progression, we included 9,628 men with an IPSS of 8–14 and no surgery, who were followed from when they first reported an IPSS of 8–14 to 2008. Progression to “severe” LUTS (N=2,557) was defined as IPSS of ≥20, surgery, or medication use. We estimated age-specific and age-standardized rates. RESULTS: Incidence and progression rates increased with age (P-trend<0.0001); progression rates were higher than incidence rates. The age-standardized rates were: incidence of moderate to worse LUTS 18.5; incidence of modest to worse LUTS 40.5; and progression to severe LUTS 44.9 per 1,000 man-years. CONCLUSIONS: LUTS incidence and progression rates are high and rise steeply as men age. These rates may be used for planning adequately powered trials to test lifestyle interventions for LUTS well before surgical or pharmacologic treatment is indicated.